Phonons of solid phases (α, β, δ, ε) of carbon monoxide by optical studies - Serdyukov, A.; Vetter, M.; Brodyanski, A.; Jodl, H.J. (Физика низких температур, 2010)
The phase diagram of solid carbon monoxide was investigated in the pressure range 0–10 GPa and temperature range 30–300 K by infrared and Raman spectroscopy. The tentative phase diagram known from literature was expanded and specified in details. The δ-phase region is divided into two subphases — δrot and δloc that is similar to the one in solid nitrogen. The pressure-temperature behavior of the elementary and combined excitations was also followed up. The vibron overtone region was carefully investigated by FTIR spectroscopy as a function of temperature at different pressures, whereas the fundamental one — by Raman spectroscopy. The features of the IR-active phonon sideband to the vibron overtone were investigated in details in the whole pressure-temperature region. The lattice-phonon spectra were studied by Raman spectroscopy as a function of pressure (at lowest temperature) and by IR spectroscopy as a function of temperature at saturated vapor pressure.